Implementasi Program Sekolah Penggerak (PSP) Dalam Meningkatkan Karakter Peserta Dididik Melalui Projek Penguatan Profil Palajar Pancasila (P5) Di SMA Negeri 18 Palembang - Bukman Lian; Murni Sinaga; Rohani, Rohana (CV. Ulil Albab Corp, 2025)
This research aims to explore and analyze the impact of implementing the Driving School Program (PSP) in improving the character of students through a project to strengthen the profile of Pancasila students at SMA Negeri 18 Palembang. This research is qualitative research with a descriptive method. The research was conducted at SMA Negeri 18 Palembang. Data collection techniques use interview methods, field observations and documentation studies. The research results reveal that the Implementation of the Driving School Program (PSP) provides direct and sustainable learning experiences in various aspects of daily life, forming strong characters from the moral, spiritual and psychological aspects of students. Then the supporting factors in implementing the program are the school's readiness to become a driving school and the inhibiting factor is the lack of teacher understanding in implementing the Driving School Program. The results of research on the Implementation of the Driving School Program (PSP) in Improving the Character of Students through the Project for Strengthening the Profile of Pancasila Students at SMA Negeri 18 Palembang highlight the importance of implementation in achieving educational goals. Implementation refers to the process of implementing planned and structured activities to achieve certain goals. Thus, the implementation of the Build Your Body and Soul Project through PSP at SMA Negeri 18 Palembang has had a broad positive impact in shaping the character of students in accordance with the values of Pancasila.